A Survey to Determine the Level of Knowledge on Chronic Pain and its Management amongst Fifth year Medical students at the University of Stellenbosch - Minaar, Izette (Stellenbosch : Stellenbosch University, 2016)
Thesis (MMed)--Stellenbosch University, 2016.